Human Autoinflammatory Diseases Mediated by NLRP3-, Pyrin-, NLRP1-, and NLRC4-Inflammasome Dysregulation Updates on Diagnosis, Treatment, and the Respective Roles of IL-1 and IL-18 - Alehashemi, Sara; Goldbach-Mansky, Raphaela (Frontiers in Immunology, 2020)
Research in the last several years led to novel findings in inflammasome biology and genetics that substantially altered the diagnosis and management of patients with autoinflammatory syndromes caused by NLRP1-, NLRP3-, NLRC4-, and Pyrin inflammasome mediated systemic inflammation and spurred the development of novel treatments. The use of next-generation sequencing in clinical practice allows for rapid diagnosis and the detection of somatic mutations that cause autoinflammatory diseases. In contrast to NLRP3, pyrin and NLRP1 inflammasomopathies, gain-of function mutations in NLRC4 cause constitutive elevation of IL-18 levels in serum that predispose to the development of macrophage activation syndrome (MAS). Insights gained from murine models and the recent characterization of novel diseases with high IL-18 serum levels, unravel the biology of “high IL-18 states” that predisposes to MAS, translate into improved diagnosis, the use of novel biomarkers that facilitate recognition and the development of novel treatments that have significantly improved the management of these conditions. Lastly, advances in structural modeling by cryo-electron microscopy (cryo-EM), characterization of post-translational modifications (PTM) that regulate inflammasome activation, and high-throughput screening (HTS) of libraries of inflammasome-inhibiting compounds promise a new generation of treatments for patients with inflammasomopathies.